Design and Analysis of Photonic Crystal Fiber with Large Negative Dispersion and Small Dispersion Slope - Singh, Rahul (My University, 2012)
Conventional optical fibers can only guide light in a high refractive index core by total internal reflection. By using total internal reflections, it is not possible to guide light in an air core. Light guidance in air is of great interest for various technological and scientific applications and has only recently been possible with the advent of photonic band gap fibers. Control of dispersion in PCFs is very important problem for realistic applications of optical fiber communications, dispersion compensation and nonlinear optics. Usually the positive dispersion of the optical fiber, which is a major factor to cause optical pulse broadening and restrict transmission distance and bandwidth, can be compensated by using dispersion compensating fiber (DCF) with large negative dispersion. The present work aims at the designing and simulation of a structure with ultra-flattened dispersion, low modal birefringence and low polarization dependent loss single mode photonic crystal fibers. By varying various parameters such as diameter of air holes (d), number of air holes rings (N), refractive index of cladding (n), hole pitch (Ʌ) analysis has been done for an optimum profile. Although the largest negative dispersion value of -31.6 ps/nm/km is calculated for d= .44 μm but desired structure has been achieved with d= .42μm, N = 8, n = 1.4, = 1.5 μm low ultra flattened dispersion in a range of -20.35 to –20.12 ps/nm/km with dispersion slope equal to -5.47x10-4 ps/nm/km within the wavelength range of 1.49 to 1.91 μm. Low modal birefringence on the order of 10^-4 and low polarization dependent loss on the order of 10^-14 is realized with the proposed PCF structure.
Keywords: Photonic Crystal Fiber